Evaluation of cell proliferation and apoptosis markers as predictive factors for electrochemotherapy in cutaneous squamous cell carcinoma of cats - Ribeiro, Roana Cecília S. [UNESP]; Anjos, Denner S. [UNESP]; Pazzini, Josiane M.; Bertolo, Paulo Henrique L. [UNESP]; Carra, Gabriel João U. [UNESP]; De Nardi, Andrigo B. [UNESP] (FapUNIFESP (SciELO), 2023)
Determining cell proliferation rates and tumor apoptosis through immunohistochemistry allows the evaluation of the biological behavior of the tumor, optimizing the patient’s clinical course. This study aimed to analyze the immunohistochemical expression of Ki-67, COX-2 and caspase-3 and correlate them with the type of response to ECT in feline cutaneous squamous cell carcinoma (SCC), thus determining the predictive potential of these variables. For this, 13 samples of feline cutaneous SCC were evaluated before ECT, and statistical analyses of the correlation intensity between the variables were performed using the Spearman correlation coefficient, with a significance level of 95%. The results indicate a significant negative correlation between histopathological grade and response to ECT (ρ=-0.6; p=0.03); there was no significant correlation between Ki-67, COX-2 and caspase-3 immunoexpression with the response to ECT (ρ=-0.18; p=0.54/ρ=-0.23; p=0.44/ρ=-0.12; p=0.69, respectively). Therefore, the study shows that the histopathological grade, tumor size and staging, degree of cellular pleomorphism and degree of inflammatory infiltrate can be considered negative prognostic factors for cutaneous SCC and negative predictors for response to ECT. However, the markers Ki-67, COX-2 and caspase-3 are not considered predictive factors for the type of response to ECT. In addition, no relationship between these immunoexpressions and greater tumor aggressiveness was observed. The SCCs evaluated in this study showed significant COX-2 labeling, indicating a potential therapeutic target. ECT has been shown to be safe and effective for local control of feline cutaneous SCC but with reduced effectiveness in larger and invasive lesions.
Marcadores de proliferação celular e de apoptose como fatores preditivos à eletroquimioterapia em carcinoma de células escamosas cutâneo de gatos
Keywords: caspase-3; cats; COX-2; electrochemotherapy; Ki-67; squamous cell carcinoma